IDENTIFIKASI RISIKO KECELAKAAN KERJA PADA PROYEK PEMBANGUNAN GEDUNG RUMAH SAKIT - Tiara Romadhona Ika Bayu Putri (Jurnal Vokasi Teknik Sipil, 2024)
Currently, there are many hospital building projects which generally carry out risky activities which can lead to undesirable events Based on a literature study, hospital building construction projects, including construction projects, have a relatively high potential risk of accidents. This is because the hospital construction project involves quite complex work. In this study, the descriptive qualitative method was used, that is descriptive qualitative research, that is a research approach carried out by dechiper or describe the meaning of information or data obtained. The writing of this research was based on risk identification obtained through literature studies from 10 previous studies and then validated through expert judgment by experts. Based on the analysis, it can be concluded that there are 34 work accident risk indicators consisting of 5 risks from excavation and embankment work, 9 risks from formwork work, 10 risks from casting work, and 10 risks from casting work. 43 work accident risk variables consisting of 5 risks from excavation and embankment work, 10 risks from formwork work, 12 risks from casting work, and 16 risks from casting work. The results of this risk identification can be used as a basis for preventing possible risks from occuring of work accidents in hospital building construction projects.